An investigation of caregivers' perceptions regarding emotional and behavioural development of twelve to eighteen year old adolescents who are living in a well-resourced South African children's home. - Fainstein, Shalya (My University, 2010)
In South Africa the incidence of orphaned and abandoned children is rising dramatically due to HIV/AIDS, poverty and unemployment, thus resulting in an excessive amount of children without appropriate primary care givers. Research has found that institutionalized children or those without significant primary caregivers, often experience problems with attachment formation and other facets of emotional and behavioural development. This qualitative study aimed to explore how caregivers experience and understand the behavioural and emotional development of adolescents who are in their care. More specifically, the candidate explored whether caregivers perceived any emotional or attachment difficulties in the adolescents, despite their financial and material needs being met. Factors relating to resilience in adolescents were examined through the eyes of the caregivers, in order to identify and understand ways in which vulnerable children and adolescents rise above adverse circumstances and develop relationships despite having had very little attachment relationships in their past. Erikson’s Developmental Theory and Bolwby’s Attachment Theory underpinned this study together with elements of Freud’s Psychosexual Theory of development. Bandura’s Theory of Self Efficacy and Resilience were included to examine theory relating to resilience in adolescents. During semi-structured interviews with caregivers, open-ended questions were used and thematic content analysis was employed to transcribe, categorize and code data from the interviews. The themes which emerged during data analysis indicated that the caregivers’ perceptions were consistent with the literature and research relating to emotional and behavioural difficulties that adolescents experience as a result of insufficient or inadequate attachment relationships with primary caregivers. The themes highlighted areas of difficulty in the adolescents’ emotional and behavioural development, however, characteristics of resilience and self-efficacy were also identified by the caregivers and considered to be positive elements influencing the adolescents’ growth and development. The researcher interacted only with the caregivers from the identified children’s home. No children or adolescents were approached or involved during the course of the research study.